A collaborative method for scoping software product lines (2019)
The definition of the scope of software product lines (Scoping SPL) is a key activity in the development of Software Product Lines (SPL), both affecting either the success or failure of the line. In order to delimit the reach of a line, different knowledge is needed that is distinct in various types of experts and roles, but it is difficult to obtain people with different knowledge and interests to interact and agree on the scope, and it is even more complex, if the results to be obtained are not clear. This research is focused on the study of a set of scoping SPL ap- proaches, and applies method engineering and collaborative engineer- ing to propose a collaborative method for SPL scoping in such a way that it provides concrete guidelines to facilitate its application as iden- tification of the artefacts to be developed with the specific templates and steps for obtaining the output artefacts that make up the scope of the SPL.